THE INFLUENCE OF THE BRAKE PADS PLACEMENT ON A FREIGHT CAR WHEEL ON THE EFFICIENCY OF BRAKES APPLICATION - Babaiev, O. M.; Danysh, P. D. (Science and Transport Progress, 2008)
The general properties of brake of the freight car of new generation have been calculated. The possible wedging of wheel pairs is being counteracted by the gear ratio computed according to minimax values of rated indices.